Predictive Maintenance Implementation In Reach Stacker Kalmar Type Drd To Reduce Component Failure - Ponidi Ponidi; Ali Makhfud (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2018)
The Reach Stacker lifting tool is the most productive lifting tool for container lifting today. It can move container till 20 container box in every hour, it means that in 3 minutes it can lift and lower 1 box container. In operation the lifting equipment will surely experience a stop operation due to the failure of a component. The purpose of this study was to determine critical and important components of the history of failure data for a year (2016) in PT meratusline, by using tools Fault Tree Analysis, Failure Mode and Effect Analysis and Pareto. From the analysis, it obtained Load Handling component as the most critical component based on the most frequent failure and required a long time to repair. The cause of the failure itself was inconsistent greasing maintenance / Predictive maintenance was not executed and there was no loose handling of Load Handling chain components. From the result of research, it was suggested to make standard rule by adding greasing item in worksheet Predictive maintenance and Standard Operating Procedure Predictive Maintenance for chain replacement on Load Hadling component if already entering 12000 Hour life.